Morphological comparison of masseter muscle fibres in the mandibular rest and open positions using diffusion tensor imaging. (5th April 2022) - Sugano, Takehiko; Ogawa, Toru; Yoda, Nobuhiro; Hashimoto, Teruo; Shobara, Kenta; Niizuma, Kuniyasu; Kawashima, Ryuta; Sasaki, Keiichi
Abstract: Background: The masseter muscle has a complicated multipennate internal structure and exhibits functional differentiation when performing various stomatognathic functions. It is important to understand the internal structural changes of the muscle during functioning to elucidate characteristic muscle disorders such as local myalgia. Diffusion tensor imaging (DTI) may be useful for investigating the internal structural features of muscle. Objectives: To evaluate the features of masseter muscle fibres in human participants using DTI fibre tractography, and to elucidate the structural differences in the masseter muscle between the mandibular rest and open positions. Methods: Five healthy men (age 31 ± 7 years) underwent DTI and T1‐weighted MRI of the right masseter muscle in the mandibular rest and open positions. MR images were used as a reference for muscle layer segmentation (superficial, intermediate, and deep). DTI fibre tractography of the masseter muscle was performed and the orientation of the DTI fibres was analysed in each layer using coordinates based on the Frankfurt horizontal plane. Results: The DTI fibre orientation of the deep layer significantly changed between the mandibular rest and open positions in the frontal plane ( p  < 0.05, Wilcoxon rank sum test). However, no significant change was found in the superficial and intermediate layers. Conclusion: DTI fibre tractography confirmed regional differences in the orientation change of the masseter muscle fibres between different mandibular positions. The results may support the existence of functional partitioning inside the masseter muscle and suggest that DTI may be useful for the evaluation of muscle fibres in multipennate muscles. Abstract : Diffusion tensor imaging (DTI) muscle fiber tractography confirmed regional differences in the orientationchange of the masseter muscle fibers between different mandibular positions, which may support the existence of functional partitioning inside the masseter muscle.